Computed Dosimeter Dose Index on a 16-Slice Computed Tomography Scanner - Tadelech S. Mekonin; Tilahun T. Deressu (SAGE Publishing, 2022)
A computed tomography dose index can be used to quantify the radiation dose received during a CT scan and it is an indicator of the radiation dose to the polymetaylenmetaAcrylate (PMMA) standardized phantom. The objective of this study was 2-fold. The first was to measure the computed tomography (CT) radiation dose for the head and body polymetaylelenmetaAcrylate (PMMA) phantoms and to determine the accuracy of the CT radiation dose parameter displayed on the CT scanner console; these were measured in this investigation and compared with the dose displayed on the CT scanner console. The dose was calculated using the formalism described in the American Association of Physics in Medicine (AAPM) Report 96. The second was to compare the dosimetric results of the head and body polymetaylelenmetaAcrylate (PMMA) phantoms with dose reference levels published in international journals, as well as to measure the central cumulative dose (DL ' (0)), as recommended by the American Association of Physics in Medicine (AAPM) report 111. This is a new, cutting-edge methodology for estimating the CT radiation dosage provided by the abdomen, thorax, and head of a PMMA phantom. We used a Philips Big Bore CT scanner with 16 slices. A CT dosimeter head phantom with a diameter of 16 cm, a CT dosimeter body phantom with a diameter of 32 cm, a 100 mm pencil chamber (PC), and a 20 mm short chamber (SC) were employed. These were coupled to an electrometer and a dosimetric readout device. The measured volume computed tomography dose index (CTDIvol) values were in good agreement with the CT radiation dose displayed on the corresponding CT scanner console. The percentage disagreement was less than 10%, with a maximal difference of 1.7% and 5.5% for the body and head phantom, respectively. The central cumulative dose (DL (0)) measurements (for L ' = 100 mm) also matched nominal or the corresponding computed tomography dose index (CT) scanner console volume computed tomography dose index (CTDIvol) values. In this case, the agreement is always below 3% for abdomen scans and 1.0% for head examinations. This result implies that the radiation dose supplied by the 16-slice computed tomography (CT) system was in good agreement with the international dose reference level and we observed something different.